2023
DOI: 10.1101/2023.10.22.563156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 50-gene high-risk profile predictive of COVID-19 and Idiopathic Pulmonary Fibrosis mortality originates from a genomic imbalance in monocyte and T-cell subsets that reverses in survivors with post-COVID-19 Interstitial Lung Disease

Bochra Tourki,
Minxue Jia,
Theodoros Karampitsakos
et al.

Abstract: Background: We aim to study the source of circulating immune cells expressing a 50-gene signature predictive of COVID-19 and IPF mortality. Methods: Whole blood and Peripheral Blood Mononuclear cells (PBMC) were obtained from 231 subjects with COVID-19, post-COVID-19-ILD, IPF and controls. We measured the 50-gene signature (nCounter, Nanostring), interleukin 6 (IL6), interferon gamma;-induced protein (IP10), secreted phosphoprotein 1 (SPP1) and transforming growth factor beta (TGF-beta) by Luminex. PCR was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Peripheral blood mononuclear cell signatures in COVID-19 lung disease and IPF have also been shown to exhibit comparable transcriptional signatures and have prognostic value ( 42 ). There is also evidence that monocyte and T cell subsets are involved in the pathogenesis of post-COVID-19 ILD; a recent study evaluating blood samples from subjects with post-COVID-19 ILD, IPF, and controls showed that survivors of post-COVID-19 ILD had higher expression of genes related to naïve and memory CD4 T cells, Tregs, memory CD8 T GZMB+, memory CD8 T GZMK+, and naïve CD8 T cells, but lower levels in IPF, suggesting most subjects with post-COVID-19 ILD have partially or completely resolved pulmonary fibrosis, while most patients with IPF have progressive disease ( 43 ). Further studies are still needed to determine the exact mechanism(s) underlying ILD after COVID-19, but the results of previous studies suggest that the complex immune response to the virus itself may promote the development of ILD after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cell signatures in COVID-19 lung disease and IPF have also been shown to exhibit comparable transcriptional signatures and have prognostic value ( 42 ). There is also evidence that monocyte and T cell subsets are involved in the pathogenesis of post-COVID-19 ILD; a recent study evaluating blood samples from subjects with post-COVID-19 ILD, IPF, and controls showed that survivors of post-COVID-19 ILD had higher expression of genes related to naïve and memory CD4 T cells, Tregs, memory CD8 T GZMB+, memory CD8 T GZMK+, and naïve CD8 T cells, but lower levels in IPF, suggesting most subjects with post-COVID-19 ILD have partially or completely resolved pulmonary fibrosis, while most patients with IPF have progressive disease ( 43 ). Further studies are still needed to determine the exact mechanism(s) underlying ILD after COVID-19, but the results of previous studies suggest that the complex immune response to the virus itself may promote the development of ILD after COVID-19.…”
Section: Discussionmentioning
confidence: 99%